Phenology of some species that are food for the White-winged Guan Penelope albipennis - Martos, Joaquín R. (2008)
The phenological traits (vegetative growth, flowering and fruiting) of 17 plant species that feed the White-winged Guan (Penelope albipennis Taczanowski) was assessed in the Ecological Reserve of Chaparrí, Chongoyape (Lambayeque). The evaluations were monthly between July 2004 and June 2005 in three areas known as: plain dry forest, dry forest to wet and dry forest ravine slope. The temperature was correlated with vegetative growth, flowering and fruiting. Of the 17 species tested, 6 species (35,3%) were available as food for White-winged Guan throughout the year, while the remaining 11 species (64,7%) were seasonal, year-round the White-winged Guan available food supply of the species evaluated.